Homestay operation under the purview of the Ministry of Tourism and Culture of Malaysia: the case of Kelantan homestay operators - Bachok, Syahriah; Hasbullah, Hafizah; Ab Rahman, Syakir Amir (Malaysian Institute of Planners, 2018)
This research outlines the selection, registration, operation and management of formal homestays under the purview of Ministry of Tourism and Culture of Malaysia. Using a case study of Kelantan, the research further elaborates on the inception of such concept in Malaysia, the process and procedures for establishment of homestay operation as well as the maintenance and upholding qualities of the current operational homestays. One of the largest contributing sectors to the Gross National Product in 2015, tourism offers great and various activities to tourists domestic and international alike. One such activities is agrotourism that provide opportunities for the visitors to stay and experience the life of an agriculture community in rural areas of Malaysia. Kelantan being one of the most remote areas in the Peninsula is still rich with natural resources and agricultural produce has the advantage of showcasing the unique attractions to various tourists’ types, especially those who were willing to stay overnight or more to properly enjoy and learn about realities of daily life of these selected communities. A gap in the literature identified that research on how these communities were selected to offer such activities while maintaining their identities are scantily available. Hence, this research aims at explaining the processes of registering of homestays and rooms for tourists stay and identifying improvement areas which can be targeted to increase the income receipts from this specialised yet diversified sector.